2016
DOI: 10.1016/j.indcrop.2016.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer improves seed and oil yield of safflower under tropical conditions

Abstract: a b s t r a c tSafflower (Carthamus tinctorius L.) has gained importance as an oilseed crop due to its hardiness and oil, which can be used in the production of biofuels. Studying proper crop management methods is highly important for the development of safflower in Brazil, since applying fertilizers correctly and using the appropriate time are efficient ways to achieve higher yield. Thus, the objective of this study was to evaluate safflower yield components, seed yield and oil content in two growing seasons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 27 publications
2
26
0
2
Order By: Relevance
“…Safflower production in Brazil is not remarkable, but current research has shown potential for cultivation (Sampaio et al., 2016; Santos, Bassegio, & Silva, 2017). Safflower could become an important crop in the Brazilian tropical conditions, which has a long dry period with high temperatures during the winter.…”
Section: Introductionmentioning
confidence: 99%
“…Safflower production in Brazil is not remarkable, but current research has shown potential for cultivation (Sampaio et al., 2016; Santos, Bassegio, & Silva, 2017). Safflower could become an important crop in the Brazilian tropical conditions, which has a long dry period with high temperatures during the winter.…”
Section: Introductionmentioning
confidence: 99%
“…This annual crop from the Asteraceae family, to which the sunflower (Helianthus annuus L.) belongs, originated somewhere between Asia and Africa [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…Santos et al (2017) observed a variation of 2.6-4.3 g in the Southwest of Brazil. Sampaio et al (2016) observed the 100-grain weight to be 6.8 g in winter and 4.8 g in autumn when cultivating IAPAR. The 100-grain weight observed for the North American cultivars in the present study was lower than that in the registered Brazilian national cultivars, because the 100-grain weight is affected by the characteristics and genetic background of the plant (Braileanu et al, 2013).…”
Section: Traits Measured At Harvestmentioning
confidence: 93%
“…Santos et al (2017) observed variation between 10 and 34 chapters for four cultivars in two types of soils. Sampaio et al (2016) observed 12 chapters in winter and 9 chapters in the autumn. The number of chapters per plant is affected by the spatial arrangement of plants, as evidenced by the fact that the number of chapters per area decreased with the increase in plant density, as reported by Vaghar et al (2014) and Sampaio et al (2017).…”
Section: Traits Measured At Harvestmentioning
confidence: 96%
See 1 more Smart Citation